1997
DOI: 10.1074/jbc.272.49.30724
|View full text |Cite
|
Sign up to set email alerts
|

A Baculovirus (Bombyx mori Nuclear Polyhedrosis Virus) Repeat Element Functions as a Powerful Constitutive Enhancer in Transfected Insect Cells

Abstract: It has been previously reported that baculovirus homologous regions, the regions of baculovirus genomes that contain the origins of DNA replication, can augment the expression of a small number of baculovirus genes in vitro. We are now reporting that a region of the genome of Bombyx mori nuclear polyhedrosis virus (Bm-NPV) containing the homologous region 3 (HR3) acts as an enhancer for the promoter of a nonviral gene, the cytoplasmic actin gene of the silkmoth B. mori. Incorporation of the HR3 sequences of Bm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 37 publications
1
79
0
Order By: Relevance
“…Earlier Habib et al (18) reported that AcMNPV hr1 enhances transcription from the polyhedrin promoter in a classic enhancer-like manner. Other BEV hrs have also been shown to display a potent enhancer function on exogenous and endogenous promoters in the absence of any viral trans-activator, suggesting that the binding of host factors might be involved in the enhancer mechanism (19). Considering the enhancing propensity of hrs to mediate transcription even without the BEV-encoded IE-1 factor, one would predict some basal level of transcription from the integrated rep genes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier Habib et al (18) reported that AcMNPV hr1 enhances transcription from the polyhedrin promoter in a classic enhancer-like manner. Other BEV hrs have also been shown to display a potent enhancer function on exogenous and endogenous promoters in the absence of any viral trans-activator, suggesting that the binding of host factors might be involved in the enhancer mechanism (19). Considering the enhancing propensity of hrs to mediate transcription even without the BEV-encoded IE-1 factor, one would predict some basal level of transcription from the integrated rep genes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression cassette pIE1/153A (23,45) was employed for expression of recombinant cystatin 1 in insect cells. Plasmid pIE1/153A.cyst was generated as follows.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Use of the IE-1 transactivator and the HR3 enhancer with the actin promoter has resulted in a more than 1000-fold increase in the stimulation of foreign gene expression through the actin promoter. 19,27 We used plasmid vectors that contained the B. mori actin promoter downstream from the BmNPV IE-1 transactivator and the BmNPV HR3 enhancer for high-level expression, together with either a blasticidin or a neomycin resistance gene for use as a selectable marker (Fig. 1).…”
mentioning
confidence: 99%